The role of public institutions and non-governmental organizations in integrated water resources management in the Bawku West District - Gumah, Akolgo Isaac (University of Development Studies, 2012)
The capacity for the implementation of the integrated water resources management framework is ignited by strong participation of various stakeholders. Such participation can create the foundation for using water resources efficiently and effectively by engaging social learning, building trust and a forum for understanding possibilities and limits. This study examined the role of public institutions and non-governmental organisations in integrated water resources management in Bawku West District. The study employed qualitative research techniques, mainly interviews and observations in the data collection. The study revealed that the decentralised departments in the district as well as some NGOs play significant roles in the management of natural resources and especially water resources. The decentralised bodies in the district formulate bye-laws regarding water resources management, educate and sensitized the people on water resources management (and all other natural resources). The NGOs engage in disaster preparedness with communities, support farmers to achieve sustainable agriculture production and educate and sensitise the local communities on water resources management. The study concludes that these institutions have the potential of enhancing water resources management at the local level but they are constrained by financial resources and logistics and recommends that they should be strengthened to enable them function effectively.